ISLAMIC BOARDING SCHOOL BUILDING DESIGN WITH A COVID-19 PROTECTION PROTOCOL - Dyah Nurwidyaningrum; Tri Wulan Sari; Sujito Sujito (Journal of Islamic Architecture, 2022)
Islamic Boarding School building functions as a place of education for prospective ulama who are expected to be the disseminators of Islamic religious knowledge to the wider community. Coronavirus transmission was very fast in 2019-2022, so Islamic boarding schools must appeal to the government’s way of learning, one of which is to comply with the Covid-19 protection protocol. This study aims to get Islamic boarding school design with Covid-19 protection protocol. The method we did was survey and observation to initial research data, then made floor plans for the first and the second floors with AutoCAD according to a related party and expert ideas. Finally, with SketchUp Pro, a standard building design for the COVID-19 health protocol was obtained, such as the design of the top, 3D, side, and inside view. The design consisted of a bedroom in 8x8 meters with a height of 4 meters for 18 students with adequate ventilation and lighting. In every room and terrace, there is Covid-19 health protocol message. The area for hand washing with soap is located in the right and left wings of the bedroom. The stairs and doors for entry and exit are different. The rooms are arranged with one-way circulation of human movement. The corridor to come through the main stairs or the area near the bathroom goes down through the stairs near the ablution place. With this arrangement of beds, students' movement in the bedroom leads to another corridor from the direction of arrival. The students sitting on the bed can see the green view. They can move without colliding with each other, so it feels more relieved. They are targeted for activities in good health and lower disease transmission. As a result, students get more breathing space and behave more responsibly for personal health. For teachers and management, it is easier to carry out transmission tracing.